MITIGATION HANDLING OF SQL INJECTION ATTACKS ON WEBSITES USING OWASP FRAMEWORK - imam riadi; Rusydi Umar; wasito sukarno (Universitas Trunojoyo Madura, 2018)
The development of the security system on the application of a website is now more advanced. But a software that has vulnerability will threaten all fields such as information system of health, defense, finance, and education. Information technology security issues will become the threat that made managers of the website (webadmin) alerted. This paper is focused on how to handle various application web attacks, especially attacks that uses SQL Injection, using The Open Web Application Security Project (OWASP), the aim is raise awareness about application security web and how to handle an occurred attack.